2019
DOI: 10.30834/kjp.31.1.2019.152
|View full text |Cite
|
Sign up to set email alerts
|

Somatic complaints and their relationship with depressive symptoms among adolescent girls: a descriptive study

Abstract: Background: Physical symptoms of unknown aetiology are common in children and adolescents. Depression in this developmental age causes significant interpersonal and psychosocial problems including the risk for suicide. Objectives: Main objectives were to assess the somatic complaints and depressive symptoms of adolescent girls and to identify the relationship between these variables. Association between somatic complaints/depressive symptoms and selected socio personal variables was also analysed. Methods: A d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Association between Somatic complaints/depressive symptoms and selected socio personal variables was also analysed. The study found a significant positive correlation between Somatic complaints and depressive symptoms 23 .…”
Section: Discussionmentioning
confidence: 71%
“…Association between Somatic complaints/depressive symptoms and selected socio personal variables was also analysed. The study found a significant positive correlation between Somatic complaints and depressive symptoms 23 .…”
Section: Discussionmentioning
confidence: 71%
“…Additionally, theories have been pursued to elucidate the mechanisms underlying somatic symptoms in EA individuals, such as the stress-leading process and its impact on pain and other complaints [ 123 ]. Thus, while somatic complaints in the student-age population may be related to depression and anxiety, nowadays the management of EA individuals, especially women with unexplained somatic symptoms, is still challenging [ 124 ]. Identification and psychological care may help to avoid somatisation disorder in terms of the full-blown form and long-term mental health problems.…”
Section: Discussionmentioning
confidence: 99%